2017
DOI: 10.1007/s13361-017-1624-0
|View full text |Cite
|
Sign up to set email alerts
|

On the SIMS Ionization Probability of Organic Molecules

Abstract: The prospect of improved secondary ion yields for secondary ion mass spectrometry (SIMS) experiments drives innovation of new primary ion sources, instrumentation, and post-ionization techniques. The largest factor affecting secondary ion efficiency is believed to be the poor ionization probability (α) of sputtered material, a value rarely measured directly, but estimated to be in some cases as low as 10. Our lab has developed a method for the direct determination of α in a SIMS experiment using laser post-ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 56 publications
0
41
0
Order By: Relevance
“…First, the properties of the primary ion beam determine the mass range of the detected molecules. 5 A higher energy of the primary ions produces higher secondary ion yield which increases sensitivity; however it causes higher fragmentation, meaning that the molecular information on the detected ions can be lost. A highly energetic beam is also more destructive to samples.…”
Section: What Inuences Sims Measurements?mentioning
confidence: 99%
“…First, the properties of the primary ion beam determine the mass range of the detected molecules. 5 A higher energy of the primary ions produces higher secondary ion yield which increases sensitivity; however it causes higher fragmentation, meaning that the molecular information on the detected ions can be lost. A highly energetic beam is also more destructive to samples.…”
Section: What Inuences Sims Measurements?mentioning
confidence: 99%
“…6,7,15,23,35 Furthermore, because the material is sputtered, it generally creates fragments that make interpreting the resultant mass spectrum more difficult, and can have differences in sputtering efficiency for different materials. 23,37 Even with these limitations, SIMS is closest to a single measurement of chemical and morphological information that is widely used by the community, but still cannot answer many questions about system morphology because of its limited spatial resolution and fragmentation of molecular species.…”
mentioning
confidence: 99%
“…At this point, we can only speculate about the reason for the changes of the ionization efficiency when going through the interface. In principle, the velocity‐integrated ionization probability measured here can be influenced by variations of the emission velocity distribution . While this dependence has been discussed (and debated) mainly for inorganic materials and ejectees, we feel that it is an unlikely cause for changes in the chemical ionization mechanism responsible for the formation of the quasi‐molecular ions studied here.…”
Section: Resultsmentioning
confidence: 79%
“…Comparing the mass resolved signal detected for a molecular secondary ion and its neutral counterpart therefore directly delivers information about the SIMS ionization probability . We have used this methodology in the past to determine the formation of molecular secondary ions for a few organic molecules sputtered from a homogeneous film . It was found that even when profiling through such a single component material, the ionization probability changes as a function of applied ion fluence due to the chemical surface modification induced by prolonged ion bombardment.…”
Section: Introductionmentioning
confidence: 99%